2021
DOI: 10.1186/s40851-021-00182-y
|View full text |Cite
|
Sign up to set email alerts
|

Detailed morphology of tentacular apparatus and central nervous system in Owenia borealis (Annelida, Oweniidae)

Abstract: The Oweniidae are marine annelids with many unusual features of organ system, development, morphology, and ultrastructure. Together with magelonids, oweniids have been placed within the Palaeoannelida, a sister group to all remaining annelids. The study of this group may increase our understanding of the early evolution of annelids (including their radiation and diversification). In the current research, the morphology and ulta-anatomy of the head region of Owenia borealis is studied by scanning electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 78 publications
3
11
0
Order By: Relevance
“…Acetylation of alpha-tubulin is widely used to detect ciliary structures in annelid, mollusk, and nemertine larvae ( Wanninger, 2015 ; Yurchenko et al, 2019 ; Magarlamov et al, 2020 ). In addition, these antibodies mark neuronal elements in some adult mollusks and annelids ( Faller et al, 2012 ; Kotsyuba et al, 2020 ; Temereva et al, 2021 ). Therefore, mollusk larvae stained only with secondary antibodies were analyzed as controls for all primary antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Acetylation of alpha-tubulin is widely used to detect ciliary structures in annelid, mollusk, and nemertine larvae ( Wanninger, 2015 ; Yurchenko et al, 2019 ; Magarlamov et al, 2020 ). In addition, these antibodies mark neuronal elements in some adult mollusks and annelids ( Faller et al, 2012 ; Kotsyuba et al, 2020 ; Temereva et al, 2021 ). Therefore, mollusk larvae stained only with secondary antibodies were analyzed as controls for all primary antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…An exact study of serial sections of the whole vessel allowed us to discover adherence junctions between cells, borders between cells, and that myofilaments are present in all myoepithelial cells, but not in certain areas of the axial vessel (Figure 3). Our study revealed that the ultrastructure of the wall of the axial and lateral vessels of B. viridis corresponds to a simple type of coelothelium, which is known in many annelids (Bartolomaeus, 1994;Fransen, 1988;Gardiner, 1992;Rieger, 1980;Temereva et al, 2021) and other bilaterians (Kuzmina et al, 2018;Rieger & Lombardi, 1987;Temereva, 2015Temereva, , 2017. The great difference between B. viridis axial vessels and blood vessels of other coelomic bilaterians is the absence of a coelomic canal around the axial vessel.…”
Section: Ultrastructure Of Blood Vesselsmentioning
confidence: 61%
“…The histological organization of proboscis blood vessels is simple: it consists of a layer of basal lamina and lacks the endothelial lining. Such a structure can be compared with blood capillaries of some other bilaterians (Kuzmina et al, 2018; Temereva & Malakhov, 2004; Temereva et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, nuchal organs and complex cup‐shaped eyes are also absent in adult specimens (Helm et al, 2022). Comparable patterns are also observable for members of the Palaeoannelida, namely the Oweniidae and Magelonidae (Beckers et al, 2019; Helm et al, 2016; Rimskaya‐Korsakova et al, 2016; Temereva et al, 2021). In all these cases observed so far, a change of lifestyle from planktonic towards sedentary is linked with a significant reduction of neuronal complexity.…”
Section: Discussionmentioning
confidence: 97%